Online recognition of Arabic handwritten words using alignments matching algorithm - Abuzaraida, Mustafa Ali (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2015)
Muslims all over the world are dealing daily with Arabic language to perform their prayers. ALLAH (SWT) swear in the holy Qura'n of saving the Qura'n until the judgment day. Although, keeping the Qura'n safe is saving Arabic language as well. However, Muslims should serve Arabic language to remain safe either from using it or by doing research on it. This research thesis aims to study the recognition of Handwritten Arabic texts in general and for online side in particular. The proposed system deals with the handwritten words as one block instead of segmenting the words into characters or strokes. The system started with collecting the dataset of 120 common Qura'nic words. These words have been gone via some phases to be ready for using. These phases are: Preprocessing, features extraction, and recognition phase. In the first phase, the words went throw some steps to be standardized. The second phase is about extracting the features of each word and to be saved then in the system database. In the third phase, the system uses matching technique to search for the testing word with the system database. The system was tested using two experiments and the results reached up to 100% which they were significantly accepted comparing with the previous works in the same criteria. Nevertheless, the methodology of the system was significant and could be acceptable.